Engaging expert in public sector: personal experience as consultant to the government agencies and international organization - El-Muhammady, Ahmad (2022)
The presentation explores the following aspects; the connection between organisational management particularly in public sector, it seeks to answer the question why government agencies, sometimes, engage with external expert. The presentation is made based on the speaker's personal experience as consultant to several government agencies and international organisation.